Functionalizing Location's Indications and Aesthetic Elements in Novel Film"(Pianist Film as an example): منير طه سلمان (Al-Academy, 2015)
Cinema artist work has not been achieved without location indications ; places are of cultured indications and its effect on behaviors and trends. Location is an important element as to convey meanings via its interaction with the personality about which it has been written may studies. Despite location occupies huge spaces within social and philosophical Drama branches , but it has a strong connection with the art world since it reflects reality of global theories in different fields. Audio and visual speech in Cinema have connected with the environmental effectiveness resulted from location which the sensual understanding interacts with in a way that suits Movie. Location consists of mixing elements of Movie and it in return interacts with location as to have a grand effect on viewers and to send aesthetic and convincing meanings to viewers. The location is part of vital elements that being used in cinema so as to produce a subject. For psychological , objective and dramatic reasons , selected locations have not come randomly, but rather come in an organized studied way as to serve developing drama. The art re-organizes location and its composition; the genius lies in giving aesthetic dimension and symbols. It is the ability of Film maker to produce a picture in which location becomes effective and active as to move the activity of location as an effective and aesthetic element depending on location 's interaction and its relation with outstanding elements . Hence, for this importance , I resort to study the effect of location in novel Drama passing through theoretical opinions of researchers and specialists. This study results in getting out group of indications that help us make analysis for outstanding filmic sample for the film of piano tuner. The research indicates to important results that form an problem needs to be explained and this problem lies in "How to functionalizeLocation's Indications and Aesthetic Elements in Novel Film"